2010
DOI: 10.1021/jp109674t
|View full text |Cite
|
Sign up to set email alerts
|

Combined Experimental and Computational Study of Intramolecular Charge Transfer In p-N,N-Dimethylamino-p′-cyano-diphenylacetylene

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions?Contact the NRC Publications Archive team at PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…Note that neither DACN-DPA nor BODIPY derivatives bearing a dimethylaminophenyl group at the meso position exhibit such CT absorption feature at low energy. [60][61][62]67,68 Fluorescence Emission and Photophysical Properties. The fluorescence emission spectra of T-1 and T-2 were obtained upon excitation at 485 nm ( Figures S4 and S5 in the Supporting Information).…”
Section: Table 1 Experimental and Calculated λ Values (Nm) And Transmentioning
confidence: 99%
“…Note that neither DACN-DPA nor BODIPY derivatives bearing a dimethylaminophenyl group at the meso position exhibit such CT absorption feature at low energy. [60][61][62]67,68 Fluorescence Emission and Photophysical Properties. The fluorescence emission spectra of T-1 and T-2 were obtained upon excitation at 485 nm ( Figures S4 and S5 in the Supporting Information).…”
Section: Table 1 Experimental and Calculated λ Values (Nm) And Transmentioning
confidence: 99%
“…By further comparing these results with ICT-based aryl amines have been designed and synthesized for potential applications in chemical sensors, fluorescence probe, and the mimicry of photosynthesis in plants. 1,[4][5][6][7][8][9] However, the mechanism for the ICT is very versatile, even controversial in some systems. 1 There is a heated debate over molecular conformation change in the ICT process, the two dominant models being the twisted intramolecular charge transfer (TICT) and planar intramolecular charge transfer (PICT).…”
mentioning
confidence: 99%
“…(3) The transient absorption spectra peaked around 500 nm at early dynamics can be assigned to the S n ← S 1 transition. (4) It is found that the formation of the PICT state is about 2 orders of magnitude faster in ACN (3.25 ps) compared to CHX (361 ps), revealing the solvent polarity dependence of the ICT state formation barrier . (5) The decay associated spectra of 978 ps obtained for DA1 in ACN reflect the absorption spectra of a twisted intramolecular charge separated state where 420 and 575 nm are assigned to benzonitrile anion and alkoxybenzene cation radical species, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…(4) It is found that the formation of the PICT state is about 2 orders of magnitude faster in ACN (3.25 ps) compared to CHX (361 ps), revealing the solvent polarity dependence of the ICT state formation barrier. 49 (5) The decay associated spectra of 978 ps obtained for DA1 in ACN reflect the absorption spectra of a twisted intramolecular charge separated state where 420 and 575 nm are assigned to benzonitrile anion and alkoxybenzene cation radical species, respectively. (6) The band around 480 nm in the nanosecond transient absorption spectra is ascribed to the T n ← T 1 transition and stabilized in ACN compared to the CHX.…”
Section: Discussionmentioning
confidence: 99%